2016
DOI: 10.1128/jb.00961-15
|View full text |Cite
|
Sign up to set email alerts
|

l-Hydroxyproline andd-Proline Catabolism in Sinorhizobium meliloti

Abstract: Sinorhizobium meliloti IMPORTANCEHydroxyproline is abundant in proteins in animal and plant tissues and serves as a carbon and a nitrogen source for bacteria in diverse environments, including the rhizosphere, compost, and the mammalian gut. While the main biochemical features of bacterial hydroxyproline catabolism were elucidated in the 1960s, the genetic and molecular details have only recently been determined. Elucidating the genetics of hydroxyproline catabolism will aid in the annotation of these genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 67 publications
(118 reference statements)
0
23
0
Order By: Relevance
“…On the other hand, the L-Hyp gene clusters of L. aggregata IAM 12614 (possibly also S. novella DSM 506) and Sinorhizobium meliloti 2011 consist of genes for T4LHyp, T3LHyp, and C3LHyp metabolism (Fig. 2D), and the L-Hyp gene cluster of L. aggregata IAM 12614 is induced by all of these L-Hyp proteins; however, they metabolize 3-hydroxy-L-prolines very poorly (13,14,18,24). Furthermore, the functional characterization of the AcnX, HypA1, and HypA2 proteins from M. viridifaciens indicated that the L-Hyp gene cluster is additionally involved in the metabolism of C3DHyp (Fig.…”
Section: R Ni Tvf Ad Gevdr Spc Gs Gt Sar Ia L R Nv Vif Ad Gevdr Spc Gmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the L-Hyp gene clusters of L. aggregata IAM 12614 (possibly also S. novella DSM 506) and Sinorhizobium meliloti 2011 consist of genes for T4LHyp, T3LHyp, and C3LHyp metabolism (Fig. 2D), and the L-Hyp gene cluster of L. aggregata IAM 12614 is induced by all of these L-Hyp proteins; however, they metabolize 3-hydroxy-L-prolines very poorly (13,14,18,24). Furthermore, the functional characterization of the AcnX, HypA1, and HypA2 proteins from M. viridifaciens indicated that the L-Hyp gene cluster is additionally involved in the metabolism of C3DHyp (Fig.…”
Section: R Ni Tvf Ad Gevdr Spc Gs Gt Sar Ia L R Nv Vif Ad Gevdr Spc Gmentioning
confidence: 99%
“…The catabolism of L-Hyp, including T4LHyp, T3LHyp, and C3LHyp, by (micro)organisms has recently been investigated at the molecular level ( Fig. 2A to C and Table 1; see also Table S1 in the supplemental material) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the purified recombinant LhpR protein binds specifically to the DNA fragments covering the lhpA regulatory region. The situation in P. aeruginosa appears to be quite different from that of S. meliloti, in which L-Hyp catabolism is regulated in a negative manner by a transcriptional regulator of the GntR (FadR) family in response to the presence of D-Hyp and D-Pro as the inducer molecule (Chen et al, 2016;White et al, 2012).…”
Section: Distinct Lhp Gene Clusters In Pseudomonad Genomesmentioning
confidence: 99%
“…24 The enzymes from this pathway have been characterized in Pseudomonas and Sinorhizobium . 20 , 25 Aerobic Hyp metabolism involves sequential oxidations of Hyp to generate α-ketoglutarate (α-KG) and ammonia, providing carbon and nitrogen for anabolic pathways (Fig. 2D).…”
Section: Introductionmentioning
confidence: 99%